Audit Delay, Financial Distress, dan Ukuran KAP sebagai Determinan Auditor Switching pada Perusahaan Sub Sektor Bank (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to examine the effect of audit delay, financial distress, and the size of the Public Accounting Firm (KAP) on auditor changes in banking sub-sector service companies listed on the Indonesia Stock Exchange (IDX) from 2020–2023. Quantitative methods and logistic regression analysis were used in this study. Secondary data were collected through purposive sampling techniques from 164 sample companies. Audit delay and KAP size were measured by dummy variables. Meanwhile, financial distress was measured by the Altman Z-Score model. The results showed that auditor switching was significantly influenced by audit delay. However, auditor switching was not significantly influenced by financial distress and the size of the auditor switching KAP. These findings indicate that audit timeliness is very important for a company's decision to change auditors.